KEPEMIMPINAN KEPALA SEKOLAH PENGARUHNYA TERHADAP KOMPETENSI, MOTIVASI, DAN KEPUASAN KERJA GURU SERTA IMPLIKASINYA TERHADAP KINERJA GURU (Penelitian pada Sekolah Menengah Kejuruan di Jawa Barat) - A. Jajang W. Mahri (Indonesian Journal of Economics and Business, 2011)
The problem in this study is that the vocational teachers in Indonesia have not been able to demonstrate the adequate work performance.  The phenomenon of high and low performance of teachers depends on variables that affect it, such as teacher competence, work motivation and job satisfaction, all of which are driven by the variable of principal’s leadership.  This study used survey approach with the type of explanation verification research on 366 teachers.  Data analysis and interpretation of the results used descriptive analysis and verification (SEM).  Results show that the principal’s leadership has a direct impact on teacher competence, work motivation of teachers, and teacher job satisfaction. However, the principal’s leadership does not imply directly to the performance of teachers, but through teacher competence, work motivation, and job satisfaction. In this way, the principal’s leadership may act more as a driver or enabler that allows an increase in competence, motivation and job satisfaction of teachers so that in turn it would improve teacher the performance.